2012
DOI: 10.1136/annrheumdis-2011-200970
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid reduces knee pain and bone marrow lesions over 1 year: a randomised controlled trial

Abstract: ACTRN 12609000399291.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
191
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(218 citation statements)
references
References 33 publications
(40 reference statements)
9
191
3
7
Order By: Relevance
“…In a previous study, elderly women treated with alendronate had less severity of knee pain, as assessed by WOMAC scores, and decreased prevalence of knee OA-related subchondral bone lesions compared with those reporting no use [51]. Similarly, a recent RCT found that zoledronic acid reduced both knee pain, as assessed by visual analog score, and total area of bone marrow edema-like abnormalities [63]. In post-hoc analysis, a greater proportion of OA patients receiving zoledronic acid achieved a clinically significant reduction in the size of bone marrow edema-like lesions at 6 months of treatment [63].…”
Section: Human Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…In a previous study, elderly women treated with alendronate had less severity of knee pain, as assessed by WOMAC scores, and decreased prevalence of knee OA-related subchondral bone lesions compared with those reporting no use [51]. Similarly, a recent RCT found that zoledronic acid reduced both knee pain, as assessed by visual analog score, and total area of bone marrow edema-like abnormalities [63]. In post-hoc analysis, a greater proportion of OA patients receiving zoledronic acid achieved a clinically significant reduction in the size of bone marrow edema-like lesions at 6 months of treatment [63].…”
Section: Human Studiesmentioning
confidence: 87%
“…Similarly, a recent RCT found that zoledronic acid reduced both knee pain, as assessed by visual analog score, and total area of bone marrow edema-like abnormalities [63]. In post-hoc analysis, a greater proportion of OA patients receiving zoledronic acid achieved a clinically significant reduction in the size of bone marrow edema-like lesions at 6 months of treatment [63].…”
Section: Human Studiesmentioning
confidence: 91%
“…Alors que résultats avec les biphosphonates par voie orale ont déçu, une étude récente, évaluant l'acide zolédronique intraveineux vs placebo chez les patients gonarthrosiques ayant un oedème médullaire sous-chondral en IRM, a montré un bénéfice à six mois du traitement actif [29]. Le ranélate de strontium, également utilisé comme agent ostéo-formateur dans l'ostéoporose, a fait l'objet d'une vaste étude randomisée vs placebo dans la gonarthrose avec à trois ans un effet tant symptomatique que structural (sur le pincement articulaire) [30].…”
Section: Vers De Nouveaux Traitementsunclassified
“…Little is known about the aetiology of OA BMLs, though fluctuation in size has been reported [10], as has response to pharmacological and mechanical intervention [11,12]. BMLs have been classified into groups based on their location and presumed mechanism of formation [13,14].…”
Section: Introductionmentioning
confidence: 99%